Toxic retrobulbar neuritis due to recurrent nonsteroidal antiinflammatory drug-exacerbated respiratory disease-based chronic sinusitis in the left sphenoid sinus: a case report - Schapher, Mirco; Brügel, Jacob; Güner, Fabian; Volbers, Bastian; Eichhorn, Philip; Agaimy, Abbas; Berger, Magdalena; Mardin, Christian; Dörfler, Arnd; Hock, Stefan (Journal of Medical Case Reports, 2023)
BACKGROUND: Abrupt visual impairment constitutes a medical urgency, necessitating an interdisciplinary diagnostic and therapeutic approach owing to the broad spectrum of potential etiologies, thereby engaging numerous medical specialties. CASE PRESENTATION: A 21-year-old Mixed White and Asian female patient, with medical history of nonsteroidal antiinflammatory drug-exacerbated respiratory disease necessitating previous sinus surgery, reported sudden monocular vision loss. Unremarkable ophthalmological examination of the fellow eye and hematological parameters, save for a slight elevation in lymphocytes and eosinophils, were observed. Imaging studies indicated recurrence of bilateral chronic rhinosinusitis with nasal polyps and a mucocele in the left sphenoid sinus, accompanied by bony structural deficits. Emergency revision sinus surgery, guided by navigation, was promptly performed. The patient received treatment with methylprednisolone, ceftriaxone, cyanocobalamin, pyridoxine, thiamine, and acetylsalicylic acid. During the hospital stay, she developed steroid-induced glaucoma, which was subsequently managed successfully. Negative microbiological swabs, along with pathohistological evidence of increased tissue eosinophilia and the patient's clinical history, led to the diagnosis of toxic retrobulbar neuritis secondary to recurrent nonsteroidal antiinflammatory drug-exacerbated respiratory disease-associated chronic rhinosinusitis of the left sphenoid sinus. CONCLUSIONS: In cases of acute unilateral vision loss, optic neuritis is a highly probable differential diagnosis and may be induced by pathologies of the paranasal sinuses. Nonsteroidal antiinflammatory drug-exacerbated respiratory disease, a subtype of chronic rhinosinusitis, is associated with type 2 inflammation, which is increasingly recognized for its role in the pathogenesis of bronchial asthma, eosinophilic esophagitis, and atopic eczema. Clinicians should consider chronic rhinosinusitis as a potential differential diagnosis in unilateral visual loss and be cognizant of the rising significance of type 2 inflammations, which are relevant to a variety of diseases.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Blindness; Case report; Inflammation mediators; Neuritis; Optic; Sinusitis